A simple age-structured, temperature-dependent population growth model of brown rice hopper (Nilaparvata lugens (Stal)) - Wei, Xiaojing; Balanza, Jane Girly; Ngoc, Vu Thi Bich; Giles, James Edward; Swaans, Cornelis (Cold Spring Harbor Laboratory, 2025)
Brown rice hopper (BRH), a key insect pest to rice, is known can change its longevity and fecundity due to rising temperature. Here we modeled the response of BRH population growth to temperature using an age-structured population growth model, based on reported responses of BRH development time, survival, and fecundity to temperature. We applied this model to predict historical level of BRH population growth in the Mekong River Delta (MRD) and compared the predictions with historically observed percentages of rice fields infested by BRH. The model was able to capture the seasonal variation in BRH infestation and the optimal temperature for BRH activities (app. 26.5 degrees C). These results highlighted the importance of temperature in regulating BRH population growth. The model, with further improvements as discussed, could be used for projecting BRH activity under rising temperatures or predicting BRH outbreaks due to seasonal temperature anomalies.